Cavity and entrance pore development in ant plant hypocotyls - Tsukaya, Hirokazu; Ohtake, Yutaka (Frontiers in Plant Science, 2023)
Some genera of Rubiaceae in South-eastern Asia are known as typical ant plants. They have large domatia, which form in well-developed hypocotyls in which ants nest. Previously, cavity formation processes were described; however, these reports were dependent on tissue sections of different individuals of different ages. No continuous time-course analyses were done because cavity formation occurs inside the thick tissues of highly swollen domatia. Here we observed cavity formation processes in ant plants by using X-ray computed tomography (CT) imaging and revealed previously overlooked features of cavity formation. Firstly, the cavity pore occurs at the hypocotyl base in not only gravity-dependent but also basal position-dependent manner. Secondly, the cavity forms prior to the start of short tunnel formation between the cavity and the pore. The cavity axis is parallel to the longitudinal axis of the hypocotyl; however, the short tunnel axis between the pore and cavity depends on gravity. Non-invasive CT scanning is a very powerful method to analyse deeply hidden morphogenic processes in organs.